Development of a Korean offshore wind power HSE risk assessment module based on systems engineering approach - Seongrae Kim; Keonwoo Nam; Taekyong Lee; Daeyoung Kang; Joon-Young Kim (International Journal of Naval Architecture and Ocean Engineering)
This study provides an in-depth comparison of various risk assessment models widely used in modern industry and proposes the most suitable models for offshore wind power risk assessment, focusing on the characteristics and requirements of the offshore wind power industry. The selection of the assessment models is based on various factors, such as the purpose of risk assessment, the stakeholder requirements, and the characteristics of offshore wind power. This study emphasizes the importance of using a combination of different risk assessment models in situations of high uncertainty. Using model-based systems engineering, risk assessment module is designed and implemented with traceability from requirements to detailed functionality. The risk assessment module supports organic conversion between risk assessment models to assess the risks of offshore wind power generation. The functionality and usability of the offshore wind risk assessment module were verified through the evaluation and the field test.